Sign order in Slovenian sign language locative constructions - Pavlič, Matic (Linguistica (Ljubljana), 2016)
In both sign and spoken languages, locative relations tend to be encoded within constructions that display the non-basic word/sign order. In addition, in such an environment, sign languages habitually use a distinct predicate type - a classifier predicate - which may independently affect the order of constituents in the sentence. In this paper, I present Slovenian Sign Language (SZJ) locative constructions, in which (i) the argument that enables spatial anchoring ("ground") precedes both the argument that requires spatial anchoring ("figure") and the predicate. At the same time, (ii) the relative order of the figure with respect to the predicate depends on the type of predicate employed: a non-classifier predicate precedes the figure, while a classifier predicate only comes after the figure.
Keywords: expressions de lieu; krajevni izrazi; langue des signes; ordre des signes; slovenski znakovni jezik; znakovni jezik; znakovni red